UJI NITRIT PADA AIR LINDI DI TEMPAT PEMPROSESAN AKHIR (TPA) SAMPAH CAHAYA KENCANA KABUPATEN BANJAR MENGGUNAKAN KOLORIMETER PORTABEL - Indra Febriandana; Emmy Sri Mahreda; Kissinger Kissinger; Fatmawati Fatmawati (EnviroScienteae, 2021)
Leachate monitoring required done periodically to know effectiveness of landfill management. Nitrite levels was one of pollution indicator parameter. Nitrite test using test kit method offers simplicity and concise testing time. This reasearch is propose to determine method validity of nitrite testing with portable colorimeter all at once measuring nitrite on landfill leachate and to construct technical strategies for decrease nitrite content on it. The reasearch be located at Cahaya Kencana landfill in Banjar Districts. Method validity of nitrite testing determined based on calibration curve linierity, aquracy, precision, and method comparation. Nitrite levels on landfill leachate are measuring on check point SP-1, SP-2, SP-3, and SP-4. Technical strategy to decrease nitrite levels arranged uses descriptive method and field survey. Method validity of nitrite test using portable colorimeter on landfill leachate sample declared valid based on determination of calibration curve linierity with correlation coefficient (r) 0,997; aquracy test obtained Recovery (R)  95%;  precision test obtained Relative Standard Deviation (RSD) 6,33%; and comparation of testing among method use independent t-test obtained Sig. (2-tailed, α 95%) value 0,968. Nitrite levels as result of measuring on leachate at Cahaya Kencana landfill in Banjar Districts shows that sample on SP-1 check point has exceed quality standard while SP-2, SP-3, dan SP-4 spot are belowed. Technical strategy that recommended are recirculation of leachate to landfill areas, aeration optimalization with added aerator to facultative pond, replace bacterial home with honeycomb biofilter media, and also apply fitoremediation at wetland pond in a way to grow Eceng Gondok (Eichhornia crassipes) plant that could lowered organic pollutant matters.